Biodiversity of Aquatic Plants in the Zarafshan River - Ibroximzoda, Sharifmurodov Karamatullo; oʻgʻli, Alavdinov Muxammad Haqaitxon (American Journal of Biodiversity, 2025)
This article analyzes the biodiversity and ecological importance of aquatic plants in the middle stream of the Zarafshan River. It provides detailed information about various plant species growing along the river’s middle stream, their role in the ecosystem, the impact of human activities, and the importance of preserving biodiversity. The aquatic plants in the middle stream of the Zarafshan River play a crucial role in maintaining ecological balance, improving water quality, and providing habitats for animals and birds. The article also discusses the influence of human activities on the biodiversity of aquatic plants, factors like climate change and soil erosion, and the need for preserving biodiversity and sustainable resource use.